Regional health inequalities: changes observed in Brazil from 2000-2016 - Albuquerque, Mariana Vercesi de; Viana, Ana Luiza d'Ávila; Lima, Luciana Dias de; Ferreira, Maria Paula; Fusaro, Edgard Rodrigues; Iozzi, Fabíola Lana (Ciência & saude coletiva, 2017)
Advances in reducing poverty and inequalities in the 2000s had a paradoxical effect in Brazil. This article examines how socioeconomic transformations, and the complexity of health services, are expressed in the regions established for planning purposes and the inter-governmental management of the Brazilian Unified Health System. An effort was made to identify and explain differences in the compositions of the 438 existing health regions and their spatial distribution by comparing situations observed in 2016 with those in 2000. Factor analysis and grouping techniques were used to construct a typology in the two years of the series, which was based on a diverse set of secondary data sources. It was found that there was an evolution in terms of income levels and service provision within the health regions, with a significant improvement in the socioeconomic conditions of the population. These results suggest that there was a positive impact from the combination of strategies related to social, economic and regional policies for the promotion of development, which generated more widespread well-being within the affected areas. However, limitations remain regarding the policies implemented for the universalization of the health system.